Taekwondo in the physical education of children with impaired health - Букова [Ludmila Bukova], Людмила Михайлівна; Белоусова [Irina Belousova], Ірина Михайлівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> The questions of the use of employments of taekwondo (WTF) are considered in the system of additional formation of schools, allowing to decide the row of tasks, directed on expansion of functional possibilities of organism and decline of general level of morbidity of children. Efficiency of application of this single combat is well-proven on the basis of study of level of physical development, functional state of the neuromuscular and cardiovascular systems, level of physical preparedness, and also level of anxiety of children. The impact of a health effect it was the increase in employment figures flexibility of the spine , increasing the level of physical fitness , coordination of movements, increase the functionality of the cardiovascular system. We engaged in taekwondo was an increase of stability and steadiness of nerve processes, removal of typical age of increased excitability. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->